Capital ratios and the Weighted Average Cost of Capital: Evidence from Chilean banks - Rodrigo Cifuentes; Tomás Gómez; Alejandro Jara R. (Latin American Journal of Central Banking (LAJCB), 2025)
This paper finds that an additional percentage point in the ratio of Common Equity Tier 1 (CET1) capital to risk-weighted assets is associated with an increase in the Weighted Average Cost of Capital (WACC) of Chilean banks by a maximum of only 11.7 basis points. This result is found by evaluating the impact of capital ratios on the return on capital and on the return on debt, following alternative empirical strategies which consider both market data and bank balance sheet information. Higher capital ratios decrease the return on banks' capital - partly because more capital makes banks less risky - in magnitudes similar to those found in the literature for other countries. Second, we study the role of capital in the return of bank debt. We see a strong impact of capital ratios on the return of subordinated debt and no effect on senior debt.
Keywords: C23; E32; G12; G21; G38; 330; Basel III; Capital requirements; Regulatory policies; Subordinated debt